Political Development of the North and East Sri Lanka: A Critical Study of Challenges and Opportunities - Ganeshalingam, K.T. (Federation of Global Tamils, 2025)
The North-East is a traditional homeland of the Eelam Tamils. The political fabric that supports language, culture, and economy has been built as a distinct entity separate from Southern Sri Lanka for many centuries. Non-violent struggles and armed struggle have been important in identifying such uniqueness in Eelam Tamil politics. The Tamil national consciousness that must withstand its extension has been facing challenges since 2009. The North and East politics is in a position to face challenges such as the fake left-wing politics of Southern Sri Lanka, the intelligence infiltration of Southern Sri Lanka, the aggressions to destroy the Tamil nation, the distortions that have arisen in the politics of the Tamil National Party, and the interests of regional and international powers. It is the responsibility of the Eelam Tamils to overcome such obstacles and protect their national unity and economic and social existence. The aim of the study is to find strategies to be implemented in the field where Eelam Tamils live and in the diaspora. The study is designed by focusing on direct observation and interviews as primary data and literature published on Eelam Tamil politics and experiences of other countries as secondary data. The study is conducted using a philosophical structured positivism and post-positivist approach and a mixed- methods research types.
Keywords: Left-wing Politics; Nationalism; New Nationalism; Political Economy; Political Party